COVID-19 in the Age of Artificial Intelligence: A Comprehensive Review - Rasheed, Jawad; Jamil, Akhtar; Hameed, Alaa Ali; Al-Turjman, Fadi; Rasheed, Ahmad; Rasheed, Jawad (Springer Heidelberg, 2021)
The recent COVID-19 pandemic, which broke at the end of the year 2019 in Wuhan, China, has infected more than 98.52 million people by today (January 23, 2021) with over 2.11 million deaths across the globe. To combat the growing pandemic on urgent basis, there is need to design effective solutions using new techniques that could exploit recent technology, such as machine learning, deep learning, big data, artificial intelligence, Internet of Things, for identification and tracking of COVID-19 cases in near real time. These technologies have offered inexpensive and rapid solution for proper screening, analyzing, prediction and tracking of COVID-19 positive cases. In this paper, a detailed review of the role of AI as a decisive tool for prognosis, analyze, and tracking the COVID-19 cases is performed. We searched various databases including Google Scholar, IEEE Library, Scopus and Web of Science using a combination of different keywords consisting of COVID-19 and AI. We have identified various applications, where AI can help healthcare practitioners in the process of identification and monitoring of COVID-19 cases. A compact summary of the corona virus cases are first highlighted, followed by the application of AI. Finally, we conclude the paper by highlighting new research directions and discuss the research challenges. Even though scientists and researchers have gathered and exchanged sufficient knowledge over last couple of months, but this structured review also examined technological perspectives while encompassing the medical aspect to help the healthcare practitioners, policymakers, decision makers, policymakers, AI scientists and virologists to quell this infectious COVID-19 pandemic outbreak. [GRAPHICS] .
Keywords: COVID-19; Deep learning; Infectious diseases; Drug discovery; Disease prediction; Machine learning; SARS-CoV-2; CONVOLUTIONAL NEURAL-NETWORK; X-RAY IMAGES; DISEASE 2019 COVID-19; CORONAVIRUS COVID-19; CHEST CT; AUTOMATIC COVID-19; DATA AUGMENTATION; DIAGNOSIS; PNEUMONIA; AI